A comparison of the United Kingdom’s and Switzerland’s healthcare financing systems for achieving equity and efficiency goals (Swiss Medical Weekly, 2025)
Healthcare financing systems in the United Kingdom and Switzerland were compared with a focus on efficiency and equity. The United Kingdom’s National Health Service employs the Beveridge model. It is predominantly funded through taxation and aims to provide free healthcare at the point of use. Switzerland’s healthcare financing system is based on the Bismarck model. This social health insurance model is structured around compulsory health plans for all residents.METHODS: Healthcare financing systems were compared using World Health Organization reports, national health statistics and peer-reviewed literature. Efficiency was evaluated using metrics including cost-effectiveness ratios and healthcare outcomes. Equity was assessed by examining disparities in access to healthcare and socioeconomic health outcomes.RESULTS: The National Health Service excels at administrative efficiency and providing equitable access to care. It faces challenges such as geographical disparities in service availability and perceptions of underfunding. Switzerland spends comparatively more on healthcare but delivers superior health outcomes. Issues arise with providing equitable care to all citizens, particularly affecting low-income and undocumented populations.CONCLUSION: The National Health Service is a leader in providing equitable healthcare but must address falling health outcomes while working within financial constraints. Switzerland demonstrates excellent healthcare outcomes and patient satisfaction but requires measures to ensure equitable service delivery. Ongoing policy adjustments are necessary to balance equity and efficiency while meeting meet new healthcare demands.